Instilação intraperitoneal de ropivacaína isolada e associada à dexmedetomidina para o controle da dor após ovariosalpingohisterectomia em gatas - Nicácio, Isabela Pícolo Guimarães Alves (2018)
The aim of this study was to investigate the analgesic effects and adverse events of the intraperitoneal (IP) instillation of ropivacaine alone and in combination with dexmedetomidine in cats undergoing ovariohysterectomy (OHE). Prospective, randomized, blinded, positively controlled clinical study. Forty-five cats aged (mean ± standard deviation) 17 ± 9 months and weighing 2.6 ± 0.5 kg. The cats were sedated intramuscularly (IM) with meperidine (6 mg kg-1) combined with acepromazine (0.05 mg kg-1). Anesthesia was induced with intravenous propofol to effect, and maintained with isoflurane in oxygen. After the establishment of general anesthesia, the cats were distributed into three treatment groups (n = 15) which consisted of the IP instillation of saline solution 0.9 % (group S), ropivacaine 0.25 % alone (1 mg kg-1, group R), and combined with dexmedetomidine (4 µg kg-1, group RD). Postoperative analgesia was assessed for 24 hours post-extubation using an Interactive Visual Analog Scale (IVAS) and the UNESP-Botucatu Multidimensional Composite Pain Scale (MCPS). Rescue analgesia was provided with IM morphine (0.1 mg kg-1) if the MCPS ≥ 6. Data were analyzed using the chi-square test, Tukey test, Kruskal-Wallis test, and Friedman test (p < 0.05). The pain scores did not differ between groups at any time point (p > 0.05). Rescue analgesia was required in 4/15, 1/15, and 1/15 of the cats in the S, R, and RD groups, respectively (p > 0.05). Intra-operative bradycardia was more frequent in the RD and R groups compared to the S group (p = 0.04). As part of a multimodal pain therapy, IP ropivacaine or its combination with dexmedetomidine produced similar analgesic effects and apparently neither treatment improved analgesia compared to saline in cats undergoing ovariohysterectomy.